Small Scale Ecology and Society: Forest-Culture of Papua Nutmeg (Myristica argentea Warb.) - Antoni Ungirwalu; San Afri Awang; Ahmad Maryudi; Priyono Suryanto (Jurnal Ilmu Kehutanan, 2019)
Identities and entities can be found in the cultural and ecological environment of a community when its members interact with each other. The Papua nutmeg (Myristica argentea Warb.) has been utilized by the Baham-Matta ethnic in the western part of Papua for centuries as part of their traditional ecological knowledge of nontimber forest products (NTFPs). However, this practice has not been scientifically constructed as part of social forestry science. Therefore, this paper seeks to contribute to an empirical understanding of the forest-culture of the local community and its implications for adaptive forest governance in West Papua. This study found that adaptive resource management has been applied to the Papua nutmeg, which is called henggi in Iha language and endemic to the tropical forest of the western part of Papua. The treatment of Papua nutmeg consists of three stages, namely pre-harvest, harvest, and post-harvest, all of which form a holistic unity which is sustainable until today. The Papuan nutmeg is traditionally managed and locally conserved using a traditional method known as the sasi system.Ekologi dan Masyarakat Skala Lokal : Hutan Budidaya Pala Papua (Myristica argentea Warb.)IntisariIdentitas dan entitas dapat ditemukan pada lingkungan budaya dan ekologi masyarakat saat mereka berinteraksi. Pala papua (Myristica argentea Warb.) telah dimanfaatakan selama berabadabad oleh etnis Baham-Matta di Papua Barat berdasarkan sistem pengetahuan ekologis tradisional sebagai bagian dari hasil hutan bukan kayu (HHBK) unggulan. Namun disayangkan fenomena ini belum dikonstruksi secara ilmiah sebagai bagian dari ilmu perhutanan sosial. Oleh karena itu makalah ini berusaha memberi kontribusi pada pemahaman empiris tentang hutan-budaya dari praktik masyarakat lokal dan implikasinya terhadap tata kelola hutan adaptif di Papua Barat. Hasil kajian ini menemukan bahwa pengelolaan sumber daya adaptif pala papua yang disebut Henggi dalam bahasa Iha adalah tumbuhan endemik yang berasal dari hutan alam tropis di Papua Barat. Pemanfaatan pala papua terdiri dari tiga tahapan yaitu pra panen, panen dan pasca panen. Pengelolaaannya masih sangat sederhana dan bersifat tradisional dengan salah satu keunggulannya adalah konservasi tradisional menggunakan sistem “Sasi”.